Brief review on pulse laser propulsion. (1st March 2018) - Yu, Haichao; Li, Hanyang; Wang, Yan; Cui, Lugui; Liu, Shuangqiang; Yang, Jun
Highlights: A brief review with respect to pulse laser propulsion is demonstrated. The breakdown regimes and propulsion modes of the pulse laser are reviewed. The propulsion applications as satellites, particle, and debris are introduced. Challenges for promoting the studies of pulse laser propulsion are discussed. Abstract: Pulse laser propulsion (PLP) is an advanced propulsion concept can be used across a variety of fields with a wide range of applications. PLP reflects superior payload as well as decreased launch costs in comparison with other conventional methods of producing thrust, such as chemical propulsion or electric propulsion. Numerous researchers have attempted to exploit the potential applications of PLP. This paper first reviews concepts relevant to PLP, including the propulsion modes, breakdown regimes, and propulsion efficiency; the propulsion targets for different materials with the pulse laser are then discussed in detail, including the propulsion of solid and liquid microspheres. PLP applications such as the driven microsatellite, target surface particle removal, and orbital debris removal are also discussed. Although the PLP has been applied to a variety of fields, further research is yet warranted to establish its application in the aerospace field.